Diagnostic investigation of parotid neoplasms: a 16-year experience of freehand fine needle aspiration cytology and ultrasound-guided core needle biopsy. Issue 2 (February 2015) - Haldar, S.; Mandalia, U.; Skelton, E.; Chow, V.; Turner, S.S.; Ramesar, K.; Tighe, D.; Williams, M.; Howlett, D.
Abstract This study aimed to examine the diagnostic yield of fine needle aspiration cytology (FNAC) and ultrasound-guided core needle biopsy (USCB) in the diagnosis of parotid neoplasia. A 16-year retrospective analysis was performed of patients entered into our pathology database with a final diagnosis of parotid neoplasia. FNAC and USCB data were compared to surgical excision where available. One hundred and twenty FNAC, 313 USCB, and 259 surgical specimens were analyzed from 397 patients. Fifty-six percent of FNAC and 4% of USCB were non-diagnostic. One hundred and thirty-two (33%) patients had a final diagnosis made by USCB and did not undergo surgery. Surgery was performed in 257 (65%) patients, 226 (88%) of whom had a preoperative biopsy. Most lesions were benign, but there were 62 parotid and 13 haematological malignancies diagnosed; false-negative results were obtained in three FNAC and two USCB samples. The sensitivity and specificity of FNAC were 70% and 89%, respectively, and for USCB were 93% and 100%, respectively. This study represents the largest series of patients with a parotid neoplasm undergoing USCB for diagnosis. USCB is highly accurate with a low non-diagnostic rate and should be considered an integral part of parotid assessment.